2016
DOI: 10.1001/jamacardio.2016.1577
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ACC/AHA and ESC Guideline Recommendations Following Trial Evidence for Statin Use in Primary Prevention of Cardiovascular Disease

Abstract: Based on this European population study, ACC/AHA and ESC prevention guidelines often did not align at the individual level. However, for one-fifth of the general population, guidelines on both sides of the Atlantic recommend statin initiation, with trial data supporting the efficacy. There should be no controversy about providing optimal preventive medication to these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
1
22
0
2
Order By: Relevance
“…Similar recommendations have been issued by the European Atherosclerotic Society (EAS), European Society of Cardiology (ESC) [53], and the European Association for the Study of Diabetes (EASD) [54]. Based on a recent European population study, ACC/AHA and ESC prevention guidelines often do not align at the individual level [55]. …”
Section: Current Treatment Guidelinesmentioning
confidence: 99%
“…Similar recommendations have been issued by the European Atherosclerotic Society (EAS), European Society of Cardiology (ESC) [53], and the European Association for the Study of Diabetes (EASD) [54]. Based on a recent European population study, ACC/AHA and ESC prevention guidelines often do not align at the individual level [55]. …”
Section: Current Treatment Guidelinesmentioning
confidence: 99%
“…22 The Rotterdam Population study showed that there was little alignment between different guidelines, including US and European guidelines, when estimating global risk for CVD but over three quarters would be recommended a statin based on recent primary prevention trial based approaches. 23 However, most of the participants in these population based studies were of white European origin.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is small group of patients (0.8%) at very high risk who are eligible by ESC, but not ACC/AHA guidelines. Those are patients with chronic kidney disease and significantly reduced renal function, as well as patients with heart failure who are not mentioned in US guidelines at all (14).…”
Section: Consequences Of Different Risk Calculation Modelsmentioning
confidence: 99%